A Theoretical Review of Rational Emotive Behavior Therapy (REBT) and Unconditional Self-Acceptance for Alleviating Maladaptive Perfectionism - Hyun Jeong Kim; Seung-Mi Choi (Korean Association of Rational Emotive and Cognitive Behavior Therapy, 2026)
This study aimed to examine the theoretical foundations and counseling implications of Unconditional Self-Acceptance (USA), a core concept of Rational Emotive Behavior Ther apy (REBT), for alleviating maladaptive perfectionism through a literature-based theoreti cal review. Relevant domestic and international studies on REBT, unconditional self-acce ptance, and maladaptive perfectionism were systematically identified and analyzed with a focus on their key concepts and theoretical relationships. The review found that maladap tive perfectionism is closely associated with irrational beliefs and conditional self-evaluat ion, in which individuals base their self-worth on achievement and performance outcome s. Unconditional self-acceptance, a fundamental principle of REBT, was identified as a k ey therapeutic mechanism that helps individuals separate their intrinsic worth from their successes and failures, thereby reducing self-criticism, perfectionistic concerns, and emoti onal distress. Furthermore, unconditional self-acceptance was found to promote psycholo gical flexibility and adaptive emotional functioning by encouraging individuals to accept themselves regardless of performance or external evaluation. Based on these findings, thi s study proposes an integrated theoretical framework linking maladaptive perfectionism, i rrational beliefs, and unconditional self-acceptance within the REBT perspective. The stu dy also provides theoretical implications for counseling practice and highlights the need f or future empirical research to develop and evaluate REBT-based intervention programs targeting maladaptive perfectionism.